2006
DOI: 10.1063/1.2360770
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated charge reversibility of gallium vacancies in GaAs

Abstract: The dominant charge state for the Ga vacancy in GaAs has been the subject of a long debate, with experiments proposing −1, −2 or −3 as the best answer. We revisit this problem using ab initio calculations to compute the effects of temperature on the Gibbs free energy of formation, and we find that the thermal dependence of the Fermi level and of the ionization levels lead to a reversal of the preferred charge state as the temperature increases. Calculating the concentrations of gallium vacancies based on these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…However, the current capabilities of parallel high-performance computing allow us to perform such calculations. A recent paper [4] serves as a good example of how full phonon calculations and thus taking into account entropy effects at high temperatures make it possible to determine the correct charge state of Ga vacancies in GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current capabilities of parallel high-performance computing allow us to perform such calculations. A recent paper [4] serves as a good example of how full phonon calculations and thus taking into account entropy effects at high temperatures make it possible to determine the correct charge state of Ga vacancies in GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…In the El-Mellouhi et al work [16] it is shown that the prevalence of a charge state of gallium vacancies is determined by the temperature and the position of the Fermi level (Fig. 2).…”
Section: Resultsmentioning
confidence: 94%
“…As for the Si-dopant GaAs, 3 Ga V − dominate for the larger temperature values -about 1200 K. Therefore, the acceleration of the resonant tunneling structure diffusion blur in the case of induffusion of Si atoms is possible. Literature sources analysis [12][13][14][15][16][17][18][19][20][21][22][23] shows that Al and Si diffusion coefficients in GaAs strongly vary depending on the conditions of heterostructure fabrication by molecular-beam epitaxy (MBE). This happens while the defect density of the grown heterostructures depends on a large number of technological factors such as the substrate temperature (600-650 °C) during MBE, chamber pressure, annealing temperature and time, defect density in the initial substrate, and many others.…”
Section: Key Engineering Materials Vol 724mentioning
confidence: 99%
“…In the case of heavily n-doped InGaAs and GaAs, the formation energy of group III vacancies (V III ) is calculated to rapidly decrease as the Fermi level is shifted near or into the conduction band resulting in a large increase in the population of vacancy defects formed by Frenkel pair formation. 6,[18][19][20][21][22] Positron annihilation studies in GaAs have experimentally shown that heavily n-type regions result in vacancy rich regions but there is otherwise limited direct evidence of vacancies in n-type InGaAs and GaAs. [23][24][25][26] Previous studies have used the growth of interstitial loops formed by ion implantation as a means to detect increases in the interstitial defect fluxes in Si and SiGe 27,28 and in this work the reduced nucleation of interstitial loops in n-type material is seemingly evidence of an increase in the vacancy population in heavily n-type InGaAs.…”
Section: Discussionmentioning
confidence: 99%